Valorisation of lignocellulosic biomass investigating different pyrolysis temperatures - Santos, João; Ouadi, Miloud; Jahangiri, Hessam; Hornung, Andreas (Journal of the Energy Institute, 2020)
Presently, sugarcane bagasse (SB) and oat hulls (OH) have a distinctive potential as a renewable source of biomass, due to its global availability, which is advantageous for producing liquid and gaseous fuels by thermochemical processes. Thermo-Catalytic Reforming (TCR) is a pyrolysis based technology for generating energy vectors (char, bio-oil and syngas) from biomass wastes. This work aims to study the conversion of SB and OH into fuels, using TCR in a 2 kg/h continuous pilot-scale reactor at different pyrolysis temperatures. The pyrolysis temperatures were studied at 400, 450 and 500 °C, while the subsequent reforming temperature remained constant at 500 °C. The bio-oil contained the highest calorific value of 33.4 and 33.5 MJ/kg for SB and OH, respectively at 500 °C pyrolysis temperature, which represented a notable increase compared to the raw material calorific value of SB and OH (16.4 and 16.0 MJ/kg, respectively), this was the result of deoxygenation reactions occurring. Furthermore, the increment of the pyrolysis temperature improved the water content, total acid number (TAN), viscosity and density of the bio-oil. The syngas and the biochar properties did not change significantly with the increase of the pyrolysis temperature. In order to use TCR bio-oil as an engine fuel, it is necessary to carry out some upgrading treatments; or blend it with fossil fuels if it is to be used as a transportation fuel. Overall, TCR is a promising future route for the valorisation of lignocellulosic residues to produce energy vectors.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Biofuel; Oat hulls; Pyrolysis; Sugarcane bagasse; Thermo-catalytic reforming